Assessment of consumption of light, “lekki” and fit products among students of dietetics - Anna Szczyrba; Marek Kardas (Annales Academiae Medicae Silesiensis, 2023)
Introduction: Light, “lekki” and fit products appear increasingly more often on the Polish market, and food producers, although they are obliged to include information on the labels of products with a reduced energy value and appropriate markings, do not always do it correctly. The lack of strict legal regulations on the naming of low-energy products gives food producers the opportunity to market products whose name may mislead consumers in terms of their nutritional and health values. The aim of this study is to assess the consumption of light, “lekki” and fit products among students of dietetics. Material and methods: An anonymous survey was conducted using an original questionnaire, in which 117 students of dietetics took part. The results were compiled using an Excel spreadsheet. Results: From the analysis of the results, people with normal body weight most often consume light products several times a month (34.9%), with excessive body weight 2–3 times a week (41.2%), and those underweight less than once a month (28.6%). Conclusions: Regardless of their degree and place of residence, students of dietetics most often consume light, “lekki” and fit products several times a month. People with a normal body weight, as well as those who pay attention and control their body weight, consume these products several times a month.